Performance evaluation of deep-ultraviolet laser-assisted Invizo 6000 and near-ultraviolet laser-assisted LEAP 5000 for a range of material systems - Lee, Chang-Gi; Chae, Byeong-Gyu; Ro, I. -Jun; Jang, Kyuseon; Kim, Nak-Kyoon; Ahn, Jae-Pyoung; Woods, Eric; Ahn, Jaemin; Park, Seong Yong; Gault, Baptiste; Kim, Se-Ho (Elsevier BV, 2026)
Atom probe tomography (APT) enables near-atomic-scale, three-dimensional elemental mapping through controlled field evaporation of surface atoms, triggered by the combined application of a DC voltage with either voltage or laser pulses. As selected laser wavelengths in atom probes transitioned from near-infrared (1050–1064 nm) toward shorter wavelengths, such as green (532 nm) and near-ultraviolet (NUV 355 nm), the quality of data improved and the range of analyzable materials expanded significantly. Recently, a new commercial atom probe (Invizo 6000) employing a deep ultraviolet (DUV) laser wavelength of 257.5 nm has been introduced. Invizo 6000 incorporates several new design elements, such as dual laser beam, einzel lens, and flat counter electrode. However, despite these substantial design modifications, systematic studies comparing its performance with conventional local electrode atom probe (LEAP) systems across different classes of materials remain scarce. In this study, various materials, including metals and oxides, were examined using commercial LEAP 5000 and Invizo 6000. The quality of the data obtained from both instruments was systematically evaluated using four key metrics: background levels, detection events, ion detection histograms, and mass-resolving power. Additionally, applying a thin coating to the prepared APT specimens was found to enhance data quality.